Strategi Pengembangan Agrowisata Kopi Arabika Desa Mengani Kecamatan Kintamani Kabupaten Bangli (Jurnal Agribisnis dan Agrowisata, 2025)
Development Strategy of Arabica Coffee Agrotourism in Mangani Village, Kintamani Distract, Bangli Regency. Mengani Village Arabica Coffee Agrotourism is an education based agrotourism located in Mengani Village, Kintamani District, Bangli Regency. This research aims to identify the internal and external factors of Mengani Village Arabica Coffee Agrotourism and later alternative strategies for developing agrotourism will be formulated. The data analysis used in this research is the IFAS Matrix, EFAS Matrix, IE Matrix and SWOT Matrix. The results of the IFAS and EFAS matrix analysis show that the highest score is the main strength, namely the existence of farmer- owned coffee plantations which can be used as a tourist attraction, the main weakness is the absence of a regular agrotourism marketing plan. Meanwhile, external factors consist of the main opportunities, namely an increase in public interest in traveling for tourism and the main threat faced by agrotourism is climate change which has a negative impact on Arabica coffee cultivation and unstable coffee prices which cause farmers to replace coffee plants with other crops. The results of this research show that Mengani Village Arabica Coffee Agrotourism has strong internal conditions in taking advantage of opportunities and overcoming threats from external parties. The results of the SWOT analysis obtained two alternative SO strategies, namely utilizing agrotourism facilities optimally to attract tourists to visit, utilizing strategic agrotourism locations and having beautiful views in marketing agrotourism. Two alternative WO strategies are, providing adequate supporting facilities for tourists to attract interest in visiting and conducting training to improve the quality of human resources in agrotourism, utilizing existing technology to create agrotourism social media accounts in designing effective promotions to form agrotourism marketing plans. One alternative strategy for ST is to optimize agrotourism with existing facilities. One alternative strategy for WT is to collaborate with tourism industry players within the region and outside the region to form tourist tour packages.
Keywords: coffee agrotourism; strategy; strategy analysis